The Opportunities and Challenges of Islam-Muhammadiyah in the Implementation of Merdeka Belajar Kampus Merdeka - Yunita Furi Aristyasari; Muhammad Chirzin; Chusnul Azhar (STAI Hubbulwathan Duri, 2023)
Merdeka Belajar Kampus Merdeka (MBKM) is a program designed to develop exceptional and prepared graduates to enter the community or the workforce. Islam-Muhammadiyah (AIK), as the speciality of Muhammadiyah colleges, seems to have